2015
DOI: 10.1111/acem.12721
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Signal Peptide-CUB-EGF Domain-containing Protein-1 (SCUBE1) in the Diagnosis of Pulmonary Embolism: A Preliminary Study

Abstract: Objectives: The diagnosis of pulmonary embolism (PE) in the emergency department still poses difficulties because symptoms and signs are nonspecific. There is a need for more reliable noninvasive diagnostic tests to support clinical suspicion before the costly invasive procedures with complication risks still used in the diagnosis of PE. Signal peptide-CUB (complement C1r/C1s, Uegf, and Bmp1)-EGF (epidermal growth factor) domain-containing protein 1 (SCUBE1) is a novel, secreted cell surface protein expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 12 publications
1
13
0
1
Order By: Relevance
“…SCUBE1 revealed 91% specificity and 82% sensitivity in patients with PE. [ 9 ] In our study, SCUBE1 levels were higher in the PE group than in the non-PE and control groups. A cutoff point of 0.49 ng/mL for SCUBE1 indicated 100% sensitivity and 64% specificity in patients with PE.…”
Section: Discussionsupporting
confidence: 42%
“…SCUBE1 revealed 91% specificity and 82% sensitivity in patients with PE. [ 9 ] In our study, SCUBE1 levels were higher in the PE group than in the non-PE and control groups. A cutoff point of 0.49 ng/mL for SCUBE1 indicated 100% sensitivity and 64% specificity in patients with PE.…”
Section: Discussionsupporting
confidence: 42%
“…21 Ülkemizde, yeni tanı almış 11 pulmoner emboli (PE) hastasının, 23 kontrol bireyi ile karşılaştırıldığı çalışmada, PE'li hastalarda ortalama SCUBE-1 düzeyi kontrol grubuna kıyasla anlamlı derecede yüksek bulunmuştur. 22 Hemodiyaliz hastalarında yapılan bir çalışmada ise SCUBE-1 düzeylerinin, hemodiyaliz hastalarında sağlıklı gruba göre ve hemodiyaliz seanslarının sonunda başlangıç düzeylerine göre anlamlı derece yüksek olduğu görülmüştür. Araştırmacılar, bu durumun trombositlerin diyaliz membranı gibi yüzeylerle teması sonrası aktive olduğu kanaatine varmışlardır.…”
Section: Discussionunclassified
“…SCUBE1 is a reliable marker of platelet activation. Previous studies have shown that SCUBE1 levels increase under conditions of platelet activation and aggregation resulting in ischemic complications (12,13,15). Turkmen et al determined that SCUBE1 levels increase rapidly in the 2nd h following acute mesenteric ischemia, rising significantly by 6 h, while Turedi et al showed that SCUBE1 increase signifi cantly 4 h after testicular torsion (15,17).…”
Section: Tab 2 Correlations Between Plasma Scube1 Sod Mda and Tasmentioning
confidence: 99%
“…These molecules are deposited inside alpha granules in inactivated platelets, are translocated to the platelet surface following activation by thrombin, are released in the form of small soluble particles, and are incorporated into thrombus (12). Previous studies have determined that SCUBE1 increases in conditions resulting in platelet activation and ischemic complications, such as acute pulmonary embolism, acute ischemic stroke, and acute testicular torsion (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%